Genotoxic effects of daily personal exposure to particle mass and number concentrations on buccal cells. (March 2018) - de Almeida, Daniela S.; da Costa, Silvano César; Ribeiro, Marcos; Moreira, Camila A.B.; Beal, Alexandra; Squizzato, Rafaela; Rudke, Anderson Paulo; Rafee, Sameh Adib Abou; Martins, Jorge A.; Palioto, Graciana Freitas; Kumar, Prashant; Martins, Leila D.
Abstract: The aim of this study is to assess personal exposure to Particle Number Concentrations (PNC) in four size ranges between 0.3 and 10 μm, and particulate matter (PM1 ; PM2.5 ; PM4 ; PM10 ) in order to evaluate possible genotoxic effects through a comet assay in buccal cells. A convenience cohort of 30 individuals from a Brazilian medium-sized city was selected. These individuals aged between 20 and 61 and worked in typical job categories (i.e., administrative, commerce, education, general services and transport). They were recruited to perform personal exposure measurements during their typical daily routine activities, totaling 240 h of sampling. The 8-h average mass concentrations in air for volunteers ranged from 2.4 to 31.8 μg m −3 for PM1, 4.2–45.1 μg m −3 for PM2.5, 7.9–66.1 μg m −3 for PM4 and from 23.1 to 131.7 μg m −3 for PM10 . The highest PNC variation was found for 0.3–0.5 range, between 14 and 181 particles cm −3, 1 to 14 particles cm −3 for the 0.5–1.0 range, 0.2 to 2 particles cm −3 for the 1.0–2.5 range, and 0.06 to 0.7 particles cm −3 for the 2.5–10 range. Volunteers in the 'education' category experienced the lowest inhaled dose of PM2.5, as opposed to those involved in 'commercial' activities with the highest doses for PM10 (1.63 μg kg −1 h −1 ) and PM2.5 (0.61 μg kg −1 h −1 ). The predominant cause for these high doses was associated with the proximity of the workplace to the street and vehicle traffic. The comet assay performed in buccal cells indicated that the volunteers in 'commerce' category experienced the highest damage to their DeoxyriboNucleic Acid (DNA) compared with the control category (i.e. 'education'). These results indicate the variability in personal exposure of the volunteers in different groups, and the potential damage to DNA was much higher for those spending time in close proximity to the vehicle sources (e.g. commercial services) leading to exposure to a higher fraction of fine particles. This study builds understanding on the exposure of people in different job categories, and provide policy makers with useful information to tackle this neglected issue. Graphical abstract: Image 1 Highlights: Association of smaller particles with buccal cells DNA damage was evidenced. Commercial activities presented the highest doses and DNA damage. Personal concentrations are higher than in the atmosphere at a fixed location. The proximity of the workplace to the vehicle traffic increases daily exposure.